2017
DOI: 10.1186/s12877-017-0538-9
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural differences in the association between access to healthcare and health outcomes among older adults in China

Abstract: BackgroundStudies have shown that inadequate access to healthcare is associated with lower levels of health and well-being in older adults. Studies have also shown significant urban-rural differences in access to healthcare in developing countries such as China. However, there is limited evidence of whether the association between access to healthcare and health outcomes differs by urban-rural residence at older ages in China.MethodsFour waves of data (2005, 2008/2009, 2011/2012, and 2014) from the largest nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
159
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(184 citation statements)
references
References 54 publications
9
159
4
1
Order By: Relevance
“…Access to healthcare is a fundamental social determinant of health that has been targeted by the World Health Organization to improve the availability and timeliness of quality healthcare [1]. Numerous studies have shown that timely and/or adequate access to healthcare promotes better health and well-being [2,3] and that inadequate access to care has been associated with greater psychological distress [4], lower levels of physical health [5], higher rates of rehospitalization [6], and overall higher risks of morbidity and mortality [3,7]. Moreover, a large body of literature has demonstrated the correlates and consequences of access to healthcare in a variety of settings and populations [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to healthcare is a fundamental social determinant of health that has been targeted by the World Health Organization to improve the availability and timeliness of quality healthcare [1]. Numerous studies have shown that timely and/or adequate access to healthcare promotes better health and well-being [2,3] and that inadequate access to care has been associated with greater psychological distress [4], lower levels of physical health [5], higher rates of rehospitalization [6], and overall higher risks of morbidity and mortality [3,7]. Moreover, a large body of literature has demonstrated the correlates and consequences of access to healthcare in a variety of settings and populations [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a large body of literature has demonstrated the correlates and consequences of access to healthcare in a variety of settings and populations [7,8]. At older ages, adequate access to healthcare is especially critical to maintaining health and preventing the onset (or exacerbation) of diseases through routine preventive care and treatments [5,9]. Older adults who lack access to healthcare are consequently less likely to receive early diagnoses, timely treatments, and other resources for healthcare that ultimately put them at higher risks of death [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates living in an environment providing access to reliable and appropriate health services is important to older adult’s feelings of security and sense of belonging . Previous studies have demonstrated that older people living in rural areas have poorer health outcomes, are more likely to experience poverty and are less likely to access health services when compared to older adults living in urban areas . In addition, findings from The Rural healthy People 2020 American study identified that having access to necessary health services was the most important rural health priority …”
Section: Introductionmentioning
confidence: 99%
“…5 Previous studies have demonstrated that older people living in rural areas have poorer health outcomes, are more likely to experience poverty and are less likely to access health services when compared to older adults living in urban areas. 6 In addition, findings from The Rural healthy People 2020 American study identified that having access to necessary health services was the most important rural health priority. 7 Neoliberal government-driven ideologies have seen a reduction in acute and hospital services in rural environments.…”
Section: Introductionmentioning
confidence: 99%